Utilization of OPC-Pumice composites for efficient heavy metals removal. Issue 6 (2nd November 2018) - Amin, M. S.; Hashem, F. S.; El-Gamal, S. M. A.
ABSTRACT: The immobilization effect of 1 and 3 mass % of Ni 2+ or Co 2+ ions on the hydration reaction of ordinary Portland cement (OPC) and ordinary Portland cement blended with 5 and 15 mass % pumice was investigated. This was done by studying the bulk density, total porosity, compressive strength as well as identifying the phase composition of the formed hydrates using X-ray diffraction (XRD) technique. In addition, leaching behaviour of Ni 2+ and Co 2+ ions was examined up to 90 days using static leaching technique. The results indicated that the incorporation of these ions causes a notable retardation for the early hydration of the OPC. This effect is more noticeable in presence cobalt ions. Besides, the retarding effect was increased by increasing the percentage of heavy metal ions incorporated in the hydrated matrix. However, for OPC-pumice blended cement pastes, the existence of Ni 2+ or Co 2+ ions resulted in an enhancement in the compressive strength values during the hydration period from 3-28 days to be comparable with the values of neat OPC pastes. This enhancement is attributed to the interaction of these ions with pumice which increases the heavy metal fixation.